The sustainable transformation of business events: Sociodemographic variables as determinants of attitudes toward sustainable academic conferences - Santos, J. A. C.; Fernández-Gámez, M. A; Guevara-Plaza, A.; Santos, M. C.; Pestana, M. H. (International Journal of Event and Festival Management, 2023)
Purpose – This study aimed to assess whether sociodemographic variables explain significant differences in attitudes towards transforming academic conferences into more sustainable events. Design/methodology/approach – An analytical model of participants' attitudes towards sustainable conferences based on literature review as well as the theories of reasoned action and planned behavior was developed and applied to a sample of 532 surveyed individuals from 68 countries who regularly attended academic conferences in the last five years prior to 2020. The results were refined using statistical and computational techniques to achieve more empirically robust conclusions. Findings – Results reveal that sociodemographic variables such as attendees' gender and age explain differences in attitudes. Women and older adults have stronger pro-environmental attitudes regarding event sustainability. On the other hand, attitudes towards more sustainable academic conferences are quite strong and positive overall. More sustainable events' venues, catering, conference materials, and accommodations strongly influence attendees' attitudes towards more sustainable conferences. The strength of attitudes was weaker towards transportation. Originality/value – To our best knowledge, this research is the first to assess whether sociodemographic variables explain significant differences in attitudes towards the sustainable transformation of academic conferences.